Price and Quantity Measurements: Theoretical Biases in Empirical Procedures - Jonathan Nitzan (The Bichler and Nitzan Archives, 1989)
The presence of qualitative changes in the nature of many commodities hinders our ability to construct meaningful price and quantity indices. This paper assesses some of the quality-change literature that seeks to resolve this problem. Several writers have endeavoured to develop objective, theory-neutral procedures designed to measure qualitative changes in some timeless, quantitative units. These measures, they argued, could be used to properly adjust ordinary price and quantity statistics for distortions introduced by quality changes. A careful examination suggests, however, that such procedures are neither objective nor free of theoretical biases. First, all existing attempts to develop `objective' commodity measures in the presence of quality changes are besieged by a constant resort – explicit or implicit – to `subjective' considerations. Second, both the idea that quality can be measured and the methods developed for that purpose are closely tied with the neoclassical theoretical paradigm, particularly with its emphasis on perfect competition and equilibrium.
Keywords: 330; consumption; equilibrium; hedonic index; hedonic regression; measurement; national accounting; neoclassical economics; perfect competition; price; quality change; technology